1970
DOI: 10.1073/pnas.67.1.366
|View full text |Cite
|
Sign up to set email alerts
|

Group-Specific Antigen Expression During Embryogenesis of the Genome of the C-Type RNA Tumor Virus: Implications for Ontogenesis and Oncogenesis

Abstract: Tests for the group-specific antigen of the C-type RNA tumor virus showed that mouse embryos of all strains tested, at some stage of development in utero , revealed detectable titers of group-specific antigen in one or more of their tissues; younger, rather than older, embryos were likely to be positive, particularly in those strains which normally reveal little or no expression of the RNA genome postnatally. The antigens were found in embryos of low-leukemia strains, free of infectious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0
3

Year Published

1971
1971
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(45 citation statements)
references
References 13 publications
5
37
0
3
Order By: Relevance
“…Some of these viruses are oncogenic. It also has been postulated that they have a role in normal life processes such as embryogenesis, cell differentiation, immunoregulation and evolution (Huebner et al, 1970;Aaronson & Stephenson, 1976;Levy, 1977;Todaro, 1978;Temin, 1982), although there is considerable controversy about some of these putative roles (Strand et al, 1977;Weinberg, 1980;Weiss, 1982;Jaenisch, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these viruses are oncogenic. It also has been postulated that they have a role in normal life processes such as embryogenesis, cell differentiation, immunoregulation and evolution (Huebner et al, 1970;Aaronson & Stephenson, 1976;Levy, 1977;Todaro, 1978;Temin, 1982), although there is considerable controversy about some of these putative roles (Strand et al, 1977;Weinberg, 1980;Weiss, 1982;Jaenisch, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, methods have become available that use immunosuppressed animals treated with antithymocyte serum (AT) and that make it possible for human tumor cells to grow in a heterologous species (6)(7)(8). The NIH Swiss mouse was chosen because, although it has gs antigen and viral information expressed (9,10), it is a strain with relatively low incidence of leukemia and has never been reported to produce complete, infectious type-C virus.…”
mentioning
confidence: 99%
“…This case, then, represents an additional example of the phenomenon described in our present study, namely that the elimination of endogenous xenotropic retroviruses coincides with the development of leukaemia. Another series of experiments suggested that retroviruses might play a role in normal cell differentiation (Lieberman et al, 1980;Huebner et al, 1970;Temin, 1974;Risser et al, 1978;Moroni et al, 1979). Moreover, the application of immunological procedures indicated that inhibition of macrophage function typically occurred concomitant with the onset of spontaneous T-cell leukaemia in AKR mice, and during the terminal phase of illness (Normann et at., 1981).…”
Section: Short Communicationsmentioning
confidence: 99%